PENGARUH TOTAL ASSET TURNOVER DAN NET PROFIT MARGIN TERHADAP RETURN ON ASSET PADA PERUSAHAAN SUB SEKTOR PABRIK TEMBAKAU YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2022 - Anugrah, Dimas; Janudin (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the partial and simultaneous influence of the independent variables, namely Total Asset Turnover and Net Profit Margin on the bound variable, namely Return On Asset. This research was conducted on Tobacco Factory Sub-Sector Companies listed on the Indonesia Stock Exchange for the 2015-2022 period. This research includes quantitative research with a causal associative research type. The sample used in this study is 4 companies with a population of 5. Purposive sampling technique. The data used is secondary data, namely the financial statements of tobacco factory sector companies listed on the Indonesia Stock Exchange. The data analysis techniques used are model estimation test, panel data regression, classical assumption test, T test, F test, and determination coefficient. The results of the study show that partially Total Asset Turnover does not have a significant influence on Return On Asset where the calculated value is 1.714251 < table 2.04523 and the significance value is 0.0984 > 0.05. while Net Profit Margin has a significant influence on Return On Asset  where the calculated value is 6.371727 > table 2.04523 and the significance value is 0.0000 < 0.05. Simultaneously, Total Asset Turnover and Net Profit Margin have a significant influence on Return On Asset  where the value of Fcal 85.32059 > Ftable is 3.33 and the significance value is 0.0000 < 0.05. The coefficient value of determination (R2) on the adjusted R Square generated from the regression model is 0.931507 or 93.15%. This means that 93.15% of the dependent variables of Return On Asset  can be affected by independent variables, namely Total Asset Turn Over and Net Profit Margin. While the remaining 6.85% was influenced by other variables that were not studied in this study.